Clinical Correlations of EEG Midline Spikes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The frequency, clinical characteristics and outcome of children with isolated midline spikes in the EEG, and comparison of those with and without epilepsy, were analyzed by researchers at Children's Hospital, Boston, MA.